2019
DOI: 10.1021/acs.jpcb.9b08307
|View full text |Cite
|
Sign up to set email alerts
|

Dimeric Molecular Structure of Molten Gallium Trichloride and a Hidden Evolution toward a Possible Liquid–Liquid Transition

Abstract: Group 13 trihalides MY 3 (M = Al, Ga, and In; Y = Cl, Br, and I) mostly having a dimeric M 2 Y 6 molecular structure in the solid state and a mixture of M 2 Y 6 dimers and MY 3 monomers in the vapor phase are potential candidates for entropy-driven liquid−liquid transition M 2 Y 6 ⇄ 2MY 3 at elevated temperatures. Using pulsed neutron diffraction and high-energy X-ray scattering supported by structural modeling, we show a dimer molecular structure of liquid GaCl 3 above the melting point at 351 K and midway be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…These distances were then converted into the Qspace. 25,32 They appear to be in excellent agreement with the experimental Q 0 (T), Figure 1d. The weak principal peak (PP1) at 2.1 Å −1 in S X (Q) decreases with increasing temperature and becomes nearly invisible above the critical point, Figure 1a.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…These distances were then converted into the Qspace. 25,32 They appear to be in excellent agreement with the experimental Q 0 (T), Figure 1d. The weak principal peak (PP1) at 2.1 Å −1 in S X (Q) decreases with increasing temperature and becomes nearly invisible above the critical point, Figure 1a.…”
Section: Resultssupporting
confidence: 82%
“…The intermolecular distances 2 r WS were calculated using the Wigner-Seitz approach r WS = ( 3 / 4 π ) V m N A 1 3 where V m is the molar volume and N A is the Avogadro constant. These distances were then converted into the Q -space. , They appear to be in excellent agreement with the experimental Q 0 ( T ), Figure d.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Further data analysis included absorption, Compton scattering, and polarization corrections using standard procedures 41 giving the total X-ray structure factor of S X (Q). 42,43…”
Section: High-energy X-ray Diffractionmentioning
confidence: 99%
“…Even a nonexhaustive search for structural evolution over the SC-M transition in liquid tellurides has shown that similar features (vanishing FSDP often shifting to higher Q) were observed in liquid Ge 0.15 Te 0.85 , 37−40 As 2 Te 3 , 41 supercooled tellurium, 23,42 Ga 2 Te 5 , and GeTe 2 (Figures S4 and S5). In contrast, a nearly invariant or slightly increasing FSDP moving in the opposite direction was reported for semiconducting liquid sulfides (As 2 S 3 , GeS 2 ), 22,43,44 selenides (P−Se, GeSe 2 ), 45−47 and chlorides (GaCl 3 ), 48 which were simply experiencing the thermal expansion without a concomitant density increase. Moreover, a presumable SC-M transition in liquid GeSe 2 above 1100 K was accompanied by a decreasing FSDP amplitude and a higher Q 0 shift, 49 which is a characteristic crossover from the typical lower-T semiconducting behavior.…”
mentioning
confidence: 91%